2017
DOI: 10.1007/s10067-017-3954-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of autologous hematopoietic stem cell mobilization and transplantation in patients with systemic sclerosis

Abstract: Autologous hematopoietic stem cell transplantation (AHSCT) is thought to be effective therapeutic approach in patients with poor prognosis systemic sclerosis; however, the toxicity remains a challenge. Between years 2003 and 2016, we enrolled 18 patients with systemic sclerosis at median age at transplant of 52 years (range 24–68). The median duration of disease before AHSCT was 14 months (range 2–85). Peripheral blood stem cells were mobilized with cyclophosphamide (CY) and granulocyte colony-stimulating fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
(21 reference statements)
0
7
0
1
Order By: Relevance
“…The age limit varied between studies from the upper limit of 40 years in an Indian study 14 to the upper limit of 70 years in a Polish cohort. 15 Four studies allowed inclusion of patients who had either skin involvement with mRSS >15 or organ involvement, [15][16][17]20 while in the other three studies, patients had to have both skin involvement and involvement of at least one major organ (heart, lung, or kidneys). 14,18,19 Patients with limited cutaneous SSc were included in one study as well, if severe pulmonary fibrosis or pulmonary hypertension was present.…”
Section: Discussionmentioning
confidence: 99%
“…The age limit varied between studies from the upper limit of 40 years in an Indian study 14 to the upper limit of 70 years in a Polish cohort. 15 Four studies allowed inclusion of patients who had either skin involvement with mRSS >15 or organ involvement, [15][16][17]20 while in the other three studies, patients had to have both skin involvement and involvement of at least one major organ (heart, lung, or kidneys). 14,18,19 Patients with limited cutaneous SSc were included in one study as well, if severe pulmonary fibrosis or pulmonary hypertension was present.…”
Section: Discussionmentioning
confidence: 99%
“…The specific effect of TBI and CYC on cardiac function needs to be better clarified to assess the contribution of each component to treatment-related outcomes. Based on the results presented by Helbig G. et al [ 22 ], the use of alemtuzumab, in association with CYC, for the conditioning phase, was associated with an increased occurrence of infections and thus it should be avoided because of high risk of developing infectious complications. Indeed, one of the main clinical unmet needs is the identification of the most effective conditioning protocol avoiding the toxicity induced by over-treatment and the concomitant increase in infection rate.…”
Section: Hsct and Ssc-ildmentioning
confidence: 99%
“…Many factors influence the outcome of transplant, and they are as follows: HSCT protocol, age of patient, disease duration before transplant, quality of life, and co-morbidities, e.g., decreased left ventricle ejection fraction (LVEF) or pulmonary arterial hypertension (PAH). The most frequent complications are viral reactivations (CMV, EBV, HSV) and opportunistic infections [ 21 , 22 , 27 , 29 ]. Reactivation may be dependent on ATG in conditioning [ 29 ] and occurs more frequently in CD34-selected patients [ 21 ] and in patients with low B cell count prior to transplant [ 29 ].…”
Section: Hsct and Ssc-ildmentioning
confidence: 99%
“…Most phase I/II studies showed stabilization or slight improvement in FVC after transplantation, and DLCO stabilization. [30][31][32][33] One study showed significant improvement for both FVC and DLCO over 5 years and another study showed that FVC and DLCO improved only in the subgroup of patients with progressive lung disease as an https://doi.org/10.2147/JBM.S338077…”
Section: Pulmonary Outcomesmentioning
confidence: 99%